Bioactive Sesquiterpenes from the Essential Oil of Thuja orientalis - Kim, Ki Hyun; Moon, Eunjung; Kim, Sun Yeou; Choi, Sang Un; Son, Mi Won; Choi, Sang Zin; Lee, Kang Ro (Planta Medica, 2013)
A phytochemical investigation on the essential oil of Thuja orientalis resulted in the isolation and identification of three new sesquiterpenes, 3α-methoxy-4α-epoxythujopsane (1), Δ3,15-4β-epoxythujopsene (2), and Δ3,4-thujopsen-2,15-diol (3), together with eight known sesquiterpenoids (4–11). The structures of these new compounds were elucidated based on spectroscopic data analyses including extensive 2D-NMR data and HR-ESIMS. The full assignments of 1H and 13C NMR chemical shifts for thujopsadiene (4) were obtained by 2D-NMR for the first time. All compounds (1–11) showed antiproliferative activities against the SK-OV-3 and SK-MEL-2 cell lines with IC50 values of 5.85–28.64 µM. In addition, compounds 1, 3, 4, 7, 8, and 9 significantly inhibited nitric oxide production in lipopolysaccharide-activated BV-2 cells with IC50 values of 3.93–17.85 µM without cell toxicity.
Keywords: Thuja orientalis; Cupressaceae; sesquiterpene; cytotoxicity; anti-inflammation